A renewal shot noise process with subexponential shot marks - Yiqing Chen (Risks, 2019)
We investigate a shot noise process with subexponential shot marks occurring at renewal epochs. Our main result is a precise asymptotic formula for its tail probability. In doing so, some recent results regarding sums of randomly weighted subexponential random variables play a crucial role.
Keywords: 330; shot noise; subexponentiality; tail probability; randomly weighted sum; renewal process